A case study on the understanding of the Workmen Compensation Act 1952 among legal foreign workers in San Mugiel Yamamura Woven Malacca / Mohd Zulfadli Mohd Hanib - Mohd Hanib, Mohd Zulfadli (2017)
This study, “A Case Study on The Understanding of the Workmen’s Compensation Act 1952 in among Legal Foreign Workers in San Mugiel Yamahura Woven Malacca”, is completed as a fulfilment of course Master of Enforcement Law (MEL). This study mainly conducted in a company name San Mugiel Yamahura Woven Malacca to look into understanding of the understanding of the Workmen’s Compensation Act 1952 in among Legal Foreign Workers in that company. There were several methods used in order to find answers and to collect facts and statistics to answer the research questions and to meet the objectives of the study. Qualitative research which is library-based was conducted to gather information and relevant data in this study. The relevant survey was done with statistics also done to look into understanding of legal foreign workers in that company The researchers have conducted interviewers with three individuals as representative from the legal foreign workers and representative from Human Resource Department of that company. Namely Tamang and Ram Bahadur who is representative from legal foreign workers and Cik Ina Jab inti Abd Jalil representative from Human Resource Department from the San Mugiel Yamahura Woven Malacca in obtaining a clearer understanding regarding of the Workmen’s Compensation Act 1952 in among Legal Foreign Workers in that company. Apart from that, the researcher also has to studied the Workmen’s Compensation Act 1952 in Malaysia with application of this Act. Overall, it is found understanding of the understanding of the Workmen’s Compensation Act 1952 in among Legal Foreign Workers in Malaysia still not sufficient. In view of that, understanding of legal workers regarding this Act will prevent from being exploitation or discrimination.